THE IMPORTANCE OF READING COMPREHENSION EXERCISE FOR INTERMEDIATE LEARNERS - Muydinova Makhliyo Numonjonovna (Zeta Repository, 2023)
“The more you read the more things you know. The more that you learn, the more places you will go.” This is a famous quote by Dr Suess. Although reading has numerous advantages, even many adults do not use it to its full potential. Let us examine some other advantages and importance of reading and how they may help the students’ growth, aside from the fact that it is necessary to read in order to survive in today’s society.